Bioaugmentation potential evaluation of a bacterial consortium composed of isolated Pseudomonas and Rhodococcus for degrading benzene, toluene and styrene in sludge and sewage. (January 2021) - Feng, Shoushuai; Gong, Liangqi; Zhang, Yanke; Tong, Yanjun; Zhang, Hailing; Zhu, Deqiang; Huang, Xing; Yang, Hailin
Graphical abstract: Highlight: BTS-degrading strains P. putida and R. ruber were isolated from industrial samples. BTS removal efficiency was improved to 92.7–97.9% by optimized bioaugmentation. Community structure analysis indicated Pseudomonas in sewage was strengthened. PCA analysis proved the close relationship between bacterial consortium and efficacy. Abstract: Bioaugmentation was conducted using a bacterial consortium of Pseudomonas putida SW-3 and Rhodococcus ruber SS-4, to test their ability to degrade benzene, toluene, and styrene (BTS). SW-3 and SS-4 were isolated from domestic sludge and sewage samples to establish a synthetic consortium with an optimized ratio of 2:1 to reach a degradation efficiency of 82.5–89.8% of BTS. The bacterial consortium was inoculated with sludge and sewage samples at a ratio of 2:1, resulting in a degradation efficiency of 97.9% and 92.7%, respectively, at a BTS concentration of 1800 mg·L −1 . Analysis of bacterial community structure following bioaugmentation indicated an increase in abundance of BTS-degrading bacteria, particularly Acinetobacter and Pseudoxanthomonas in sludge and Pseudomonas in sewage, enhancing the collective BTS degradation ability of the bacterial community. Principal component analysis demonstrated that a more balanced bacterial community structure was established following intervention. This indicated that the selected bacteria are excellent candidates for bioaugmentation.